Pharmacoinvasive Therapy in Treating Acute STEMI Patients in Covid-19 Era (Cardiovascular Journal, 2023)
Background: Treating acute ST segment elevated myocardial infarction (STEMI) patients by primary PCI (pPCI) has dramatically fallen globally in covid era as there is chances of potential threat of spreading COVID among the non-COVID patients. Thereby, thrombolysis of acute STEMI patient in grey zone till COVID RT PCR report to come, was the mode of treatment of acute myocardial infarction patient in our hospital. We have carried out this prospective observational study to see the outcomes of thrombolysis and subsequent intervention.Methods: STEMI patient who presented to our emergency department with chest pain and ECG and hs-Troponin-I evidenced acute STEMI, were enrolled in the study. Total 139 patients enrolled (Male:120, Female :54); average age for Male: 54 yrs., female was: 56yrs. All patients were admitted in the grey zone of CCU where thrombolysis was done.  COVID-19 patients were excluded from intervention and managed conservatively. Covid Negative patients were kept transferred to CCU green zone. On average 2.1 days after Fibrinolysis, elective PCI carried out. Data analysis from 48 patients who underwent pharmacoinvasive therapy was done.Results: Among the study population, Covid-19 positive was in 11 (7.9%) patients and Covid-19 was negative in 128 (92.1%) patients. Primary PCI was performed in 7 (5.03%) patients. Rest of the patients were managed by Pharmacoinvasive therapy. Thrombolysis by Tenecteplase (TNK) was done in 89 (64%) patients, and by Streptokinase in 25 (17.9%) patients, 18 (12.9%) patients did not receive any thrombolysis due to late presentation. Chest pain to needle time was 7.2 ±12.7hrs., thrombolysis to balloon time was 117.5 ±314.8hrs. More than 50% stenosis resolution observed in 20 (41.6%) patients, chest pain resolution within one hour of thrombolysis observed in 21 (43.8%) patients. Ten (20.8%) patients developed. Door to needle time was 30 mins. Total, 88 stents were deployed in 83 territories. CABG was recommended for 7 (5.03%) patients. Stented territory was LAD 37 (45.7%) and RCA 32 (39.5%) and LCX 12 (14.8%).Conclusion: In the era of COVID-19, in this prospective cohort study, on acute STEMI patient management, we found that Pharmacoinvasive therapy, reduced patients’ symptoms and ST resolution occurred partially.Cardiovasc j 2023; 15(2): 136-143